Protective Effect of XinJiaCongRongTuSiZiWan on the Reproductive Toxicity of Female Rats Induced by Triptolide. (6th June 2022) - Deng, Disi; Yan, Jin; Li, Wanjing; Wu, Yeke; Wu, Keming
Abstract : Background . Although triptolide (TP) has been widely used for the treatment of inflammatory, autoimmune diseases, and various kinds of tumors, the long experimental and clinical applications have exhibited severe reproductive system toxicity in TP-treated animals and patients. More importantly, the underlying molecular mechanism involved in TP-induced reproductive system toxicity still needs more research. Methods . Adult female Sprague Dawley rats and human ovarian granulosa cell lines were treated with TP and then treated with XinJiaCongRongTuSiZiWan (XJCRTSZW). Histological analysis and follicle count were executed using H&E staining. Hormone (E2, AMH, FSH, LH, and INH B) concentrations, inflammation indicators (IL-1 β, IL-6, and TNF- α ), oxidative stress indicators (SOD, GSH-Px, and MDA), apoptosis rate, protein distribution and expression (SIRT1, AMPK, and 8-OhdG), cell viability, relative protein levels (beclin-1, LC3-II/LC3-I, p62, procaspase-3, cleaved caspase-3, p-SIRT1, SIRT1, p-AMPK α -1, AMPK α -1, Akt, and p-Akt), autophagosome were detected by ELISA, commercial biochemical detection kits, flow cytometry, immunohistochemistry, CCK-8, western blotting, and transmission electron microscope, respectively. Results . XJCRTSZW administration notably improved the TP-treated pathological symptoms, including few mature follicles in the ovary and less granular cell layer, and disordered the arrangement of the follicle, lymphocytes and plasma cells infiltration, and necrosis, shedding, and follicular cystic dilatation of the granular layer follicle cells in the ovarian stroma. Furthermore, XJCRTSZW treatment observably enhanced the TP-induced reduction of primary follicles and secondary follicles numbers and decreased the TP-induced elevation of atretic follicle numbers and the expression of AMPK, SIRT1, and 8-OhdG in GCs in vivo . Moreover, XJCRTSZW application significantly increased the TP-induced diminishment of E2, AMH, and LNH-B concentrations, apoptosis rate, SOD and GSH-Px concentrations, and p62 protein level; however, it declined the TP-induced augmentation of MDA level, the levels of IL-1 β, IL-6, and TNF- α, autophagosome, beclin-1, LC3-II/LC3-I, cleaved-caspase-3, p-AMPK α -1, and p-SIRT1 protein levels both in vivo and in vitro . Besides, XJCRTSZW treatment prominently enhanced the TP-induced decrease of cell viability in vitro . Conclusion . XJCRTSZW can alleviate TP-induced reproductive toxicity via apoptosis, inflammation, and oxidative stress both in vivo and in vitro . Moreover, XJCRTSZW ameliorates TP-induced reproductive toxicity through AMPK/SIRT and Akt signaling axis mediated autophagy both in vivo and in vitro .